Power Relation In Memoirs Of Geisha And The Dancer - Mundi Rahayu; Lia Emelda; Siti Aisyah (IAIN Salatiga, 2014)
This article aims at comparing the ideas of power relation between themain female character and ―Mother‖ in Arthur Golden‘s Memoirs ofGeisha and Ahmad Tohari‘s The Dancer. These two novels share thesame main female character of traditional entertainers, as a Japanese geisha and a Javanese traditional dancer, respectively. As an entertainer in the traditional sphere, they are bounded with the other women and build close interaction as well as power relation with them who are called ―Mother‖ in the Geisha and ―ronggeng shaman‖ in The Dancer. Thepower relation between them are unique and dynamics. This is analyzed through Foucault‘s theory of power. The result of the analysis shows that the power relation is not stable, and the power practiced by each of them is influenced by the symbolic capital and economic capital they have. The negotiation and contestation come up between the actors in dailypractices as geisha and the mother, as the ―ronggeng‖ and the shaman. As the entertainers, the geisha and ―ronggeng‖ build and shape their body and performance to attract men. This geisha and ronggeng culture reproduce many other cultural product such as ―mizuage‖ in geisha, and ―bukak klambu‖ in ―ronggeng‖ both of which refer to the same thing, selling the woman‘s virginity to the highest bidder. In geisha it is used to benefit the Mother of Okiya and no rebellion of the geisha. On the other hand, Srintil does rebellious action in this ―bukak klambu‖ occasion. There seems to be different message from these two novels, The Dancer is much more questioning the norms covering the ―ronggeng‖ tradition while the Memoirs of Geisha tends to be accepting the geisha tradition as what it is.Keywords: Power Relation; Geisha ; Ronggeng ; Norms